(untitled) (Principles and Practice of Clinical Research, 2022)
Introduction: Pain is the cardinal symptom in women living with primary dysmenorrhea (PDM), resulting in a relentless negative effect on their quality of life. Women with PDM have higher levels of prostaglandin in their endometrial fluid, which correlates with the degree of pain. The standard of care treatment for pain associated with PDM starts with nonsteroidal anti-inflammatory drugs (NSAIDs) that block prostaglandin-triggering enzymes. Although NSAIDs present as a feasible option, they are also associated with a significant risk of side effects. Around 20 to 25% of patients will experience pain refractory to NSAIDs and will then seek alternative therapies. Cannabidiol (CBD) is a well-tolerated potential therapy for several chronic diseases, including pain, and acts by blocking prostaglandin-triggering enzymes, similarly to NSAIDs. The safety of CBD is well established, with the advantage of it acting via central and peripheral mechanisms. To date, no previous trials assessing CBD alone for dysmenorrhea have been conducted. Objective: To evaluate the effect of CBD alone in the reduction of acute menstrual pain compared to ibuprofen, as assessed by the total pain relief (TOTPAR) scale. Design: Randomized (with random block sizes), triple-blinded, multicenter, parallel-group, non-inferiority clinical trial. Setting: St. George, Scarborough, and Mississauga campuses at the University of Toronto, Ontario, Canada. Participants: PDM patients aged 18 to 40 years, regular menstrual cycles (ranging from 21 to 35 days), and a visual analog scale (VAS) score of ≥ 5. Intervention: 108 patients will be randomized with an allocation ratio of 1:1 to either CBD 200 mg/day or ibuprofen 800mg/day. The sample size is based on a mean expected pain relief for ibuprofen of 16.49 and CBD of 14.02, as assessed by the TOTPAR scale and on a 30% estimated dropout rate. Main Outcome Measures: The primary outcome will be the mean difference in the TOTPAR scale (range, 0-4) after taking the study drugs over four menstrual cycles. TOTPAR will be assessed after 1, 2, 3, 4, 5, and 6 hours after taking the study drugs. Secondary outcomes include pain VAS, adverse events, the need for breakthrough medications, and quality of life (QoL). Discussion: NSAIDs may cause troubling side effects, and CBD is well tolerated in clinical trials, with acceptable adverse event profiles. Numerous randomized clinical trials have demonstrated the safety and efficacy of CBD in alleviating central and peripheral pain of other disorders. The results of this trial aim to provide much-needed evidence that oral CBD alone is an alternative for the treatment of menstrual pain in women with PDM. CBD presents as an important promise for women with PDM who do not respond or who have contraindications to NSAIDs. Keywords: Cannabidiol, CBD, menstrual pain, ibuprofen, pain relief, non-inferiority, dysmenorrhea